Any time that a negative number is being multipled by another negative number, it equals a positive number. In this case, -1 multiplied by -1 equals 1. Another example of this is -5 multiplied by -5 which equals 25. Though if you multiply a negative by a positve, it equals a negative. If you were to multiply a positive by a positve, it will always equal a positve.
1
0 because X= -1
7=x+1 6=x
1+x=dd+x so dd=1 so d=1 1+x=89b+x so 89b=1 so b=1/89 bc+x=1+x so bc=1 so c=1/(1/89) = 89 so cd=89 (and x=88)
solution: y = 0 x = -1
1
0 because X= -1
7=x+1 6=x
To solve the equation 1 + 2x + 13 = 9, you first need to simplify by combining like terms. Subtract 1 and 13 from both sides of the equation to isolate the variable term. This gives you 2x = -5. Finally, divide by 2 on both sides to solve for x, which gives you x = -5/2 or -2.5.
x = 0
1+x=dd+x so dd=1 so d=1 1+x=89b+x so 89b=1 so b=1/89 bc+x=1+x so bc=1 so c=1/(1/89) = 89 so cd=89 (and x=88)
(1, 9)
y=x+1 there for answer is 2
solution: y = 0 x = -1
x(x + 1)
The coordinates of the x intercept for the equation y equals x plus 1 is (x=-1, y=0).
5x+1